Homonimia wśród nominatów dotyczących czasu i przestrzeni: polskorosyjskie studium kontrastywne - Król, Martyna (Respectus Philologicus, 2016)
The article is devoted to the problem of interlanguage homonymy. Resulting from the analysis of Polish and Russian nominates (words and phrasemes) in time and space, there have been selected four groups of interlanguage homonyms: proper homonyms (as well known as the simple ones), homonymoidal homonyms, idiomatic homonyms and culture homonyms. Special attention should be paid to the homonymoidal type of interlanguage homonymy, as this type of homonymy covers the cases of meaning inadequacies of words having very similar meanings in both analysed languages, and in formal-descriptive linguistics, those words are described as ambiguous. The practice in interlanguage contacts shows that the axiom concerning the language polysemy has a very negative influence on the acquisition of the so-called ambiguous lexemes of a foreign language by contributing to the process of identification of a certain form with all the meanings associated with this form in the native language. Hence, here comes to being the postulate to treat lexemes as monosemantic language units and obligatorily use the new notion “homonymoid”, which, according to the author, may replace the notion of “polysemy” as referred to the relations of systemic nominative units.